Tanggung Jawab Perusahaan Terhadap Kehilangan Barang Penumpang Yang Berada Di Dalam Kapal Di Panipahan Kecamatan Pasir Limau Kapas - Muhammad Danel; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The study with the title "Corporate Responsibility for Loss of Passenger Goods that Are Inside theShip in Panipahan, Pasir Limau Kapas Sub-District" aims to determine the Company's responsibility forpassenger goods and to know the resolution of goods suffered by passengers. This research includesempirical legal research.The research is to find out the business actors' responsibility for losing luggage of passengers whoare inside the ship, while the research data comes from primary data and secondary data obtained by meansof interviews with the company and related parties. Problems arise where there is a clause in thetransportation document (passenger ticket) which states that the transport company is not responsible forloss or damage during the trip. This is clearly contrary to Article 40 Paragraph (1) of Law Number 17 Year2008 concerning Shipping.The conclusion from the results of this study is that the attitude of discipline in carrying out the rulesof transporters, passengers and the government in order to create safe, comfortable and orderly services, toimprove shipping quality that prioritizes comfort, security and order, transport companies should beresponsible because they have clearly the transport agreement is made between the transport company andthe passenger. The shipping company must also include baggage documents and label the passengerbaggage so that it is not exchanged and easily prove that the transport company must also pay attention tothe Law related to the future in carrying out its business activities in order to advance sea transportationand remain a passenger choice transportation. The transportation company in the future should makecompensation provisions to see the initial agreement between the transport company and the passenger andpay attention to the compensation mechanism that has been regulated in the Act so as not to cause harm topassengers.Keywords: Responsibility, Compensation, Company, Sea Freight, Freight Agreement.